Recent Trends on Study of History of Islam in Indonesia - Fahmi, Rizqi Anfanni (Journal of Philology and Historical Review, 2024)
This article explores recent developments in the study of the history of Islam in Indonesia, highlighting methodological shifts and thematic expansions among scholars. Contemporary historiography has moved beyond traditional emphases on political and institutional narratives to embrace more nuanced explorations of Islam’s social, cultural, and local manifestations. Recent research reflects a paradigm shift from grand narratives toward micro-histories that capture the diverse expressions of Islam across regions. The increased utilization of local sources—such as manuscripts, colonial archives, and oral traditions—has enriched the understanding of Islamic dynamics in Indonesia. Employing interdisciplinary approaches that draw on anthropology, sociology, and cultural studies, the study of Islamic history has become more complex and inclusive. These trends not only advance academic discourse but also contribute to shaping a dynamic and context-sensitive Islamic identity within the Indonesian archipelago. This study adopts a qualitative literature review method by analyzing peer-reviewed scholarly articles published between 2015 and 2023, primarily sourced from the Scopus database. The analysis employs thematic coding to synthesize key findings across four main domains: historical foundations, Islamic organizations, education, and legal frameworks. This approach enables a comprehensive understanding of contemporary historiographical trends in the study of Islam in Indonesia.